COVID-19: challenges faced by Nepalese migrants living in Japan - Bhandari, Divya (BMC Public Health, 2021)
BACKGROUND: Worldwide, COVID-19 has exacerbated the vulnerability of migrants, impacting many facets of their lives. Nepalese make up one of the largest groups of migrants residing in Japan. Crises, such as the ongoing COVID-19 pandemic could disproportionately affect migrants from low- and middle-income countries like Nepal, widening health and economic inequalities. An in-depth, comprehensive assessment is needed to appraise the diverse problems they encounter. Drawing upon qualitative interviews, this study aimed to identify challenges faced by Nepalese migrants in Japan as a consequence of the COVID-19 pandemic and to discuss their needs to counter these challenges. METHODS: This qualitative study employed an interpretivist approach to appraise the first-hand experience of Nepalese migrants living in Japan. Fourteen participants (8 males and 6 females, aged 21 to 47 years old) were recruited to participate in semi-structured in-depth telephone interviews (45–60 min) regarding: (a) their perceived current physical and mental health, (b) problems faced as a result of the COVID-19 pandemic, and (c) perception of available and necessary support structures. Purposive and snowball sampling techniques were used to recruit the participants. Interviews were recorded, transcribed, and thematically analyzed. RESULTS: Six themes were identified: 1) experiencing psychosomatic symptoms, 2) adoption of new healthy behaviors, 3) financial hardship, 4) family concerns, 5) reflections on discrimination and 6) reflections of existing support and expectations of support systems. The findings of our study illustrate the specific impact of COVID-19 among Nepalese migrants regarding their unstable employment conditions, perceived lack of social support, possible obligation to send money home, difficulty in accessing services due to the language barrier, and a lack of effective governmental support from Nepal. Pandemic-related adversity has negatively impacted migrants’ mental well-being, exacerbating their vulnerability. CONCLUSIONS: Comprehensive and timely support should be provided to the vulnerable migrant population. Effective coordination among relevant parties in both countries, including the governments concerned, should be facilitated. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12889-021-10796-8.